Energy transition: Looking at village perceptions of the energy independent village program in Mojokerto Regency - Rinayuhani, Tri Ratna; Arisandi, Rachman Sidharta; Sutrisno, Eko (Journal of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: The Indonesian government has set a new renewable energy target of 23% by 2024, which will play an important role in the energy transition program, particularly in rural areas. This study describes the village government's perception of energy transition through the energy-independent village program in Mojokerto Regency. Research methodology: This article examines village government perceptions of energy transition using descriptive qualitative research, and the theory of social capital is an analytical tool for viewing village perceptions in Mojokerto Regency in realizing an energy-independent village. Results: Findings revealed that most village governments in Mojokerto Regency do not prioritize energy transition, perceiving it as secondary to poverty reduction, infrastructure improvement, and economic empowerment. Although some villages have initiated renewable energy projects, such as biogas in Pacet and micro-hydropower plants in Seloliman, Jembul, and Kebontunggul, these initiatives remain limited and fragmented. Village governments still view energy transition as resource-intensive, requiring substantial funding, technology, and external support. Conclusions: This study concludes that traditional development perspectives emphasizing physical infrastructure and economic growth dominate village agendas, thereby sidelining renewable energy programs. Without alignment between central, regional, and village policies, the realization of energy-independent villages will remain slow and ineffective. Contribution:  This research will be input to the government of Mojokerto Regency on the issue of energy transition, as well as for the central government through the Ministry of Villages in assessing the village's ability to face the energy transition process. Limitations: Because only a few villages are discussed in this study, this limitation will be balanced with an overview of other villages.